The Impact of Customer Relationship, Satisfaction, and Brand Image on Loyalty at Ryandini's Chicken Claw Business in Sei Sijenggi - Kanaya Trinazwa; Suhaila Husna Samosir; Rukmini Rukmini; Muhammad Dani Habra (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
This study aims to identify and measure the influence of customer relationships, customer satisfaction, and brand image on customer loyalty at Ryandini’s Sweet Chicken Claw business, located in Sei Sijenggi Village, Hamlet III, Perbaungan District, Serdang Bedagai Regency. A quantitative research method was employed, with data collected through observation, documentation, and questionnaires. The questionnaires used a Likert scale as a measurement tool to assess respondents’ opinions accurately. Data analysis was conducted using several stages, including validity and reliability tests, classical assumption testing, and multiple linear regression analysis, processed through SPSS version 22. These methods were used to ensure the validity of the instrument and the consistency of the findings. The research findings demonstrate that customer relationships have a significant and positive effect on customer loyalty. Customers who feel connected and valued by the business are more likely to remain loyal. Likewise, customer satisfaction—reflecting the extent to which customers' expectations are met or exceeded—has a strong and positive influence on loyalty. In addition, the brand image of the business, which encompasses customer perceptions and reputation of the product, also significantly influences loyalty in a positive direction. Furthermore, the simultaneous analysis of customer relationships, customer satisfaction, and brand image shows that all three variables jointly have a significant and positive impact on customer loyalty. This means that enhancing these three factors can strengthen customer retention and long-term commitment. These results provide valuable insights for small business owners in the food and beverage industry. Focusing on building strong relationships with customers, consistently delivering satisfaction, and maintaining a positive brand image are essential strategies to increase loyalty. For Ryandini’s Sweet Chicken Claw and similar businesses, these findings offer practical guidance for developing customer-centered marketing strategies in an increasingly competitive market.